MEDIUM-TERM RESULTS OF THE USE OF MODULAR, CEMENTLESS, PROXIMALLY PLASMA-COATED WITH DISPERSED TITANIUM POWDER AND HYDROXYAPATITE, ANATOMICAL FEMORAL STEM - Spas Radev; Hristo Petrichev; Valentin Petrov; Petko Ganev; Valeri Stavrev (Journal of IMAB)
Objective: To report the medium-term outcome of a modular, cementless, proximal hydroxyapatite-coated, anatomical femoral stem in total hip arthroplasty (THA). Methods: 160 consecutive patients aged 42 to 92 years (average 70) years underwent 185 cementless arthroplasties for primary osteoarthritis or femoral neck fractures. All procedures were performed by a single surgeon using the same modular, cementless, proximally plasma-coated with dispersed titanium powder and additionally superimposed hydroxyapatite, anatomical femoral stem, regardless of age and bone quality. The clinical assessment (pain, range of motion and walking ability) is based on the results of the Merle d'Aubigne and Postel scales. Stem failure is defined as revision or impending revision due to aseptic loosening or pain. Of the 160 patients, 21 died, and none were lost for follow-up. In 3 of the 21 patients, the femoral stems were revised for periprosthetic fractures after a fall at 6 weeks, 10 months, and 3.8 years. 138 patients (162 arthroplasties) completed a median follow-up of 7.8 (range, 5.5–10.4) years. Their overall average Merle d'Aubigne and Postel scores increased from 7.09 before surgery to 16.36 after surgery. There were 5 periprosthetic fractures of the femur, 2 deep infections, 3 dislocations, and 2 aseptic loosenings (one each for the femoral stem and acetabulum). Conclusion: The MBA femoral stem provides predictably stable fixation with an excellent medium-term result.